2016
DOI: 10.1111/jmwh.12394
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Newborn Outcomes Following Waterbirth: The Midwives Alliance of North America Statistics Project, 2004 to 2009 Cohort

Abstract: Introduction: Data on the safety of waterbirth in the United States are lacking. Methods:We used data from the Midwives Alliance of North America Statistics Project, birth years 2004 to 2009. We compared outcomes of neonates born underwater waterbirth (n = 6534), neonates not born underwater nonwaterbirth (n = 10,290), and neonates whose mothers intended a waterbirth but did not have one intended waterbirth (n = 1573). Neonatal outcomes included a 5-minute Apgar score of less than 7, neonatal hospital transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
6
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(94 citation statements)
references
References 58 publications
2
75
6
11
Order By: Relevance
“…Various studies have found that water birth is associated with decreased trauma, 10 increased trauma, 13 increased trauma in some groups of women but not others, 12 and either decreased 10 or the same 12 likelihood of extensive trauma such as 3rd/4th degree lacerations. Various studies have found that water birth is associated with decreased trauma, 10 increased trauma, 13 increased trauma in some groups of women but not others, 12 and either decreased 10 or the same 12 likelihood of extensive trauma such as 3rd/4th degree lacerations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various studies have found that water birth is associated with decreased trauma, 10 increased trauma, 13 increased trauma in some groups of women but not others, 12 and either decreased 10 or the same 12 likelihood of extensive trauma such as 3rd/4th degree lacerations. Various studies have found that water birth is associated with decreased trauma, 10 increased trauma, 13 increased trauma in some groups of women but not others, 12 and either decreased 10 or the same 12 likelihood of extensive trauma such as 3rd/4th degree lacerations.…”
Section: Discussionmentioning
confidence: 99%
“…One observational study found that water birth was associated with lower rates of 3rd/4th degree lacerations, and higher rates of birth "without injuries." 13 Compared with nonwater birth, water birth was associated with an increase in genital tract trauma, representing all episiotomies and lacerations. 11 Henderson et al 12 found that water birth was associated with more second degree lacerations among nulliparous, but not parous women.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…16,17 C. Perineal laceration. Waterbirth is associated with a decreased rate of third-and fourth-degree perineal lacerations [7][8][9]18 ; however, waterbirth may slightly increase the risk of less significant perineal trauma. However, if the tub is not cleaned properly or harbors unusual organisms such as Pseudomonas or Legionella, the woman and/or neonate could acquire an atypical infection.…”
Section: Risksmentioning
confidence: 99%
“…No maternal deaths have been reported, and only isolated fetal deaths have been attributed to immersion during labor or birth. 12,13,[16][17][18] VI. STANDARD REQUIREMENTS TO FACILITATE HYDROTHERAPY During the prenatal period, health care providers should discuss the potential use of water during labor and/or birth with all low-risk women as part of an overall discussion and education regarding evidencebased options for pain relief.…”
Section: Risksmentioning
confidence: 99%